Plan parcial de desarrollo del espacio público en función a la articulación de los servicios ecosistémicos a través de la relación urbano rural en Gigante - Huila (2023)
In the municipality of Gigante - Huila, Colombia, the dynamics of ecotourism and the recognition of the cultural landscape in rural areas have increased, promoting tourism development in the municipality with a cultural, economic and social focus. However, we seek to counteract the low visibility that the municipality has had in the coffee labor market, involving the economy and development of the population and also to provide a solution, generating strategies such as linking ecosystem services, allowing the territorial development of the population with an urban-rural relationship. With this, it is intended to evaluate the dynamics of agricultural and tourist productivity, based on the understanding of the ecosystemic services and the peri-urban relationship; where the collection of information becomes a main tool, which allows the study of the target population, to be represented in the farmers, tourists and users of the urban area, which is determined under a mixed methodology approach, in which the collection of information that is directly related to know the profile of the target population and the territorial transformation of the municipality, under a descriptive and exploratory methodology, is established.